基于符号函数的多智能体系统的分布式广义跟踪方法 (2023)
本发明提供一种基于符号函数的多智能体系统的分布式广义跟踪方法，涉及控制和信息技术领域。该方法首先构造描述多智能体系统的网络结构图，并确定该拓扑结构的邻接矩阵；建立多智能体系统的状态方程；定义描述智能体所要跟踪的时变参考信号函数值的目标函数；根据多智能体的系统邻接矩阵、状态方程和目标函数设计分布式算法；设定多智能体系统中各智能体的初始状态信息与时变参考信号信息，运行设计的分布式算法，控制每个智能体跟踪上一组时变参考信号的某一函数值；根据运行结果不断修正分布式算法，直至达到控制目标。本发明方法使得智能体系统中所有智能体可以独立地执行任务，并且在仅使用局部信息的情况下跟踪一组时变参考信号的函数值。 The invention provides a distributed generalized tracking method of a multi-agent system based on a sign function, and relates to the technical field of control and information. The method comprises:firstly, constructing a network structure diagram for describing a multi-agent system, and determining an adjacent matrix of a topological structure; establishing a state equation of the multi-agent system; defining an objective function for describing a function value of a time-varying reference signal to be tracked by the intelligent agent; designing a distributed algorithm according to the multi-agent system adjacency matrix, the state equation and the target function; setting initial state information and time-varyi